Improving the fig fruits growth and quality by spraying with extracts of moringa leaves and garlic cloves - Sara Hamied Taha; Ali Omar Aljabary (مجلة جامعة كركوك للعلوم الزراعية)
This study in a private orchard at Zardak village in the Altun Kupri district, Kirkuk Governorate,Iraq on 27 of the "Khalobaziani" local fig trees was conducted in 2021. The trees were sprayedwith Moringa leaves extract (MLE) at (0, 2, and 4 ml.L-1) and Garlic cloves extract (GCE) at (0,10 and 20 ml.L-1) until complete wetness. Randomized Complete Block Design (RCBD) wasutilized within the factorial experiments with two factors with three replicates. Results showed thattrees sprayed with all concentrations of both extracts caused an increase in the diameter of the fruitmore than in the control fruits. Significant differences in all properties studied were observed inthe fruits sprayed with 2 and 4 ml.L-1 of MLE and 10 and 20 ml.L-1 of GCE they significantlydistinguished over the control treatment in the fruit moisture content, TSS, TSS/TA ratio, glucose,fructose, vitamin C and pH. while the control treatment recorded the lowest fruit moisture content,TSS, TSS/TA ratio, glucose and fructose content, vitamin C, and pH. Moreover, a significantdecrease in fruits TA content was found due to spraying with MLE or GCE compared to the controltreatment